Recent trends in the regime of extreme rainfall in the Central Sahel. (25th March 2014) - Panthou, G.; Vischel, T.; Lebel, T.
ABSTRACT Ongoing global warming raises the hypothesis of an intensification of the hydrological cycle, extreme rainfall events becoming more frequent. However, the strong time–space variability of extreme rainfall makes it difficult to detect meaningful trends in the regime of their occurrence for recent years. Using an integrated regional approach, it is shown that over the last 10 years, the Sahelian rainfall regime is characterized by a lasting deficit of the number of rainy days, while at the same time the extreme rainfall occurrence is on the rise. As a consequence, the proportion of annual rainfall associated with extreme rainfall has increased from 17% in 1970–1990 to 19% in 1991–2000 and to 21% in 2001–2010. This tends to support the idea that a more extreme climate has been observed over 2001–2010: this climate is drier in the sense of a persisting deficit of rainfall occurrence compared to 1950–1969, while at the same time there is an increased probability of extreme daily rainfall.